Effect of Pulsating Current on 304HCU GTAW Joints - Tushar Singh Tomar (International Journal of Engineering and Management Research, 2022)
Super 304HCu super austenitic stainless-steel tubes containing 2.3 to 3 (Wt.%) Copper (Cu) are used in high temperature tubes and reheating of nuclear power plants. In general, stainless steel austenitic welded by conventional gas tungsten arc welding (CC-GTAW) now produces solid column grains, alloy disintegration and may result in lower mechanical properties. Pulsed current gas tungsten arc welding (PCGTAW) can control the formation of solids by altering the existing gradients in the weld. Super 304HCu OD 60.5 mm tubes and 3.5 mm wall thickness are automatically welded using CC and PC-GTAW processes. The joints can be detected using optical microscopy, a robust machine and a Vickers microhardness tester. The thermal properties of weld joints were tested and associated with their sub-structural features.